Oral Anticoagulants Initiation in Patients with Atrial Fibrillation: Real-World Data from a Population-Based Cohort - Rodríguez-Bernal, Clara L.; Hurtado, Isabel; García-Sempere, Aníbal; Peiró, Salvador; Sanfélix-Gimeno, Gabriel (Frontiers in Pharmacology, 2017)
Objective: Little is known about initial prescription of currently used oral anticoagulants (OAC), and correlated characteristics in real-world practice. We aimed to assess patterns of initiation of Vitamin K antagonists (VKA) and non-VKA oral anticoagulants (NOAC) in naive patients with non-valvular atrial fibrillation and the factors associated with starting treatment with NOAC. Methods: Population-based retrospective cohort study of all patients with NVAF who had a first prescription of OAC from November 2011 to February 2014 in the Valencia region, Spain (n=21,881). Temporal trends of OAC initiation are described for the whole population and by type of OAC and therapeutic agent. Factors associated with starting treatment with NOAC (vs. VKA) were identified using logistic multivariate regression models. Results: Among the patients initiating OAC, 25% started with NOAC two years after market release. Regarding temporal trends, prescription of NOAC doubled during the study period. VKA prescription also increased (by around 13%), resulting in a 30% rise in total treatment initiation with OAC during 2011-2014. NOAC initiation (vs. VKA) was associated with a lower baseline risk of thromboembolism and higher income. Conclusions: In this Spanish population-based cohort, initiation of OAC therapy saw a rapid increase, mainly but not exclusively, due to a two-fold rise in the use of NOAC. Initiation with NOAC was associated with a lower baseline risk of thromboembolism and higher income, which opposes the indications of NOAC use and reflects disparities in care. Inadequate prescription patterns might threaten the effectiveness and safety of these therapies, thus monitoring OAC prescription is necessary and should be setting-specific.